Sistema integrado de monitoramento de fronteiras em perspectiva - Israel de Oliveira Andrade; Juliano da Silva Cortinhas; Matheus Augusto Soares; Luiz Gustavo Aversa Franco (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– With one of the largest territories in the world and a very extensive land border, surveillance and monitoring of this region are especially challenging for the Brazilian state. To overcome this challenge, the Integrated Border Monitoring System (SISFRON), the world's largest system of the kind, has been conceived and is in the process of implementation (although still in pilot project). Thus, the objective of this study is to analyze SISFRON in terms of its viability, effectiveness and conjunctural importance, considering the benefits it proposes to generate, mainly in the areas of politics, economics, technology, environment, civil society, National Defense and public security.
Keywords: F52; J18; H50; 330; Brazilian Army; SISFRON; borders; National Defense; public policy